'It is pleasing to know that football can be devoted to charitable purposes': British football and charity 1870–1918. Issue 3 (15th March 2016) - Vamplew, Wray
Abstract: Football charity matches and tournaments played a significant role in the development of the sport in Britain, overlapping the era of friendly games and the coming of competitive leagues. The football community prided itself on its contributions to charity, raising more money than any other sport before 1918, and stakeholders within the game – associations, clubs, players and patrons – gained kudos for this perceived altruism. However, the amounts donated, though welcomed by the recipients, were relatively minor sources of revenue for both institutions and individuals. Moreover, the charity match became less important to clubs in an era of growing professionalism and commercialization.